Lysosomal Disorders Associated with Leukoencephalopathy - Renaud, Deborah L. (Seminars in Neurology, 2012)
Metachromatic leukodystrophy and Krabbe's disease are among the most widely recognized causes of leukodystrophy. However, white matter changes have been described in several other lysosomal storage disorders. These conditions are summarized and those associated with hypomyelination are reviewed in more detail.
Keywords: leukoencephalopathy; leukodystrophy; lysosomal storage disorder